Education of Muslim Girls Barriers, Challenges and Possibilities - Nuna, Anita (JOURNAL OF INDIAN EDUCATION, 2013)
This paper attempts to trace barriers that compel Muslim girls to discontinue their schooling at the secondary stage i.e. classes IX or X in four districts namely Bahraich, Bareilly, Bijnor and Rampur of Uttar Pradesh, based on case studies with Muslim girls aged 15–17 who had completed elementary education, but were withdrawn from schools and focus group discussions with Muslim community. Evidences from many research studies show non–availability of secondary level schooling facilities, especially in rural areas, school ethos, if available and household poverty in sending girls to schools are very important barriers that compel Muslim girls not to avail the benefits of educational opportunities at the secondary stage. Although all of these have strengths to influence parents to deprive their daughters from availing educational facilities, especially once girls attain puberty. But the argument here is that parental disinterest in Muslim girls’ education is one of the significant barriers, especially when girls attain puberty. The paper explores the potentially serious problems that lead to parental disinterest with regard to Muslim girls’ education at the secondary stage.